Upswing of German economy prevails - Ferdinand Fichtner; Guido Baldi; Franziska Bremus; Karl Brenke; Christian Dreger; Hella Engerer; Christoph Große Steffen; Simon Junker; Claus Michelsen; Katharina Pijnenburg; Maximilian Podstawski; Malte Rieth; et al. (DIW Economic Bulletin, 2015)
The German economy is continuing on an upward trend. Due to surprisingly weak production at the start of this year, GDP is likely to increase by 1.8 percent and is therefore growing somewhat slower this year than previously predicted. Growth of 1.9 percent is still expected for the coming year. After an unexpectedly weak first quarter, the global economy is expected to regain momentum as the year progresses. While growth in the emerging economies increased only slowly, both cyclically and structurally, recovery will primarily be driven by positive consumer spending in industrialized countries. With low inflation and an improving labor market situation in those countries, household income and purchasing power are likely to increase. The global economy's average annual growth rate is predicted to reach 3.5 percent in 2015 and 4.0 percent in 2016. Inflation is expected to remain at two percent this year and increase to three percent next year. Germany's strong domestic economy is driving growth. Most recently, additional social benefits and, above all, low inflation temporarily boosted real incomes; nevertheless, consumer spending will increase substantially going forward due to favorable developments in the labor market. Companies are moderately expanding their investment in equipment; however, uncertainties related to the crisis in the euro area, geopolitical tensions, and concerns about economic development in important emerging countries have a dampening effect. Exports are benefiting from the global economic recovery and temporarily also from the depreciation of the euro; overall, the stimulus from net foreign trade is likely to be modest.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook